Methane Adsorption-Desorption Hysteresis and Its Effect on Shale Gas Production - Ekundayo, Jamiu Mufutau (Curtin University, 2020)
Production of gas from shale reservoirs is governed by multiphysics mechanisms of which gas desorption is dominant. However, the actual contributions of desorption to gas production is often masked by the use of adsorption isotherms for gas production predictions. This is because it is hitherto believed that both processes are identical for methane at reservoir conditions. This research aims to quantify the effect of such a misrepresentation on gas production where sorption hysteresis is observed.